Effect of fermentation by Pediococcus pentosaceus and Staphylococcus carnosus on the metabolite profile of sausages. (December 2022) - Zhao, Yinfeng; Zhou, Chunyan; Ning, Jiawen; Wang, Shu; Nie, Qing; Wang, Wei; Zhang, Jiamin; Ji, Lili
Graphical abstract: Highlights: Metabolomics analysis of sausage's volatile and non-volatile metabolites. Characteristic flavor substances after fermentation were ascertained. Uncovering the pathways regulated by P. pentosaceus and S. carnosus. Characteristic flavor substances and non-volatile metabolites were correlated. Abstract: A multi-omics approach was applied to investigate the differences and correlations between characteristic volatile flavor substances and non-volatile metabolites in sausages fermented by Pediococcus pentosaceus ( P. pentosaceus ) and Staphylococcus carnosus ( S. carnosus ) alone and in a mixture. Twenty-seven volatile metabolites were identified by headspace solid-phase microextraction/gas chromatography-mass. According to orthogonal projections to latent structures–differential analysis, 17 characteristic volatile metabolites were detected in the sausages of different treatments. Utilizing ultra-high-performance liquid chromatography coupled with a mass spectrometer to analyze metabolite profiles, 42.03% of the non-volatile metabolites were classified as lipids and lipid-like molecules, 25.00% of organic acids and derivatives, and others. Seventeen characteristic flavor substances were significantly correlated with twenty differential non-volatile metabolites, and the non-volatile metabolites changed significantly. Differences in the characteristics and combinations of microorganisms themselves have a decisive role in the development of flavor substances and non-volatile metabolites in sausages.